The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1159/000320207
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo at Injection Site of PEG-IFN-α 2a in Two Patients with Chronic Hepatitis C: Case Report and Literature Review

Abstract: A 72-year-old female and a 57-year-old male with chronic hepatitis C were treated with a combination therapy of pegylated interferon (PEG-IFN)-α 2a (180 µg s.c. once a week) and ribavirin (1,000 mg orally daily). This resulted in the destruction of melanocytes at the injection site in both patients. In the male patient, the depigmentation progressed to the surrounding skin area. The dermatologist concurred with vitiligo as the diagnosis in both patients. Injection and surrounding site vitiligo associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…However, the mRNA of type II IFN, IFN-γ, remained below the detection limit in our biopsy samples. In contrast, recent evidences suggest that type I IFNs play a role in vitiligo pathogenesis: IFN-α producing plasmacytoid dendritic cells infiltrate active vitiligo skin ( 16 , 36 ); pegylated IFN-α2a and IFN-α2b, which are used in the treatment of chronic hepatitis C, induce depigmentation at the injection sites ( 37 ), and vitiligo patches have been observed at the site of application of imiquimod, a Toll-like receptor (TLR)-7 and TLR-8 agonist that enhances IFN-α production ( 16 ). In addition to CXCL10, IFN-induced IFIH1 was upregulated in vitiligo skin in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mRNA of type II IFN, IFN-γ, remained below the detection limit in our biopsy samples. In contrast, recent evidences suggest that type I IFNs play a role in vitiligo pathogenesis: IFN-α producing plasmacytoid dendritic cells infiltrate active vitiligo skin ( 16 , 36 ); pegylated IFN-α2a and IFN-α2b, which are used in the treatment of chronic hepatitis C, induce depigmentation at the injection sites ( 37 ), and vitiligo patches have been observed at the site of application of imiquimod, a Toll-like receptor (TLR)-7 and TLR-8 agonist that enhances IFN-α production ( 16 ). In addition to CXCL10, IFN-induced IFIH1 was upregulated in vitiligo skin in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the authors questioned whether the vitiligo represented an allergic reaction. Furthermore, depigmentation has been observed following subcutaneous pegylated interferon alpha 2a treatment for chronic hepatitis in two cases and after a steroid joint injection in another . All of these documented cases may be related to the Koebner phenomenon.…”
Section: Discussionmentioning
confidence: 94%
“…Vitiligo is a depigmenting skin condition which is more common among people with T1DM and is thought to be of autoimmune pathology. However, research suggests that patients more commonly develop hyperpigmented lesions resembling acanthosis nigricans . Allergy to insulin or its preservatives usually presents as erythema, pruritus and induration at the site of injection as a type 1, IgE mediated, hypersensitivity reaction …”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature suggests that dermatological adverse reactions induced by pegylated IFN-a plus ribaverin (RBV) are various and frequent. Generalized eczema, hyperpigmented skin and tongue lesionsmultiple fixed drug eruption, vitiligopruritis, eruption, erythema, and hair shedding, eczema-like skin lesions, photosensitivity, vesicle erythematous eruptions, pruritic papular erythematous eruptionssecondary to combined treatment with peginterferon alfa-2a and ribavirin had been reported [9][10][11][12][13][14][15][16][17]. Tavakoli-Tabasi and Bagree [18] made a longitudinal cohort study, and suggested mucocutaneous reactions during IFN and ribavirin treatment of hepatitis C are associated with HIV infection and use of pegylated IFN.…”
Section: Interferon-αmentioning
confidence: 99%